2020
DOI: 10.1093/ckj/sfaa208
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkalemia excursions are associated with an increased risk of mortality and hospitalizations in hemodialysis patients

Abstract: Background Hyperkalemia is common among hemodialysis (HD) patients and has been associated with adverse clinical outcomes. Previous studies considered a single serum potassium (K) measurement or time-averaged values, but serum K excursions out of the target range may be more reflective of true hyperkalemia events. We assessed whether hyperkalemia excursions lead to an elevated risk of adverse clinical outcomes. Methods Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 51 publications
1
28
0
1
Order By: Relevance
“…The current study also demonstrated that increased sK + variability may be a risk factor for MACE compared with low sK + variability, independent of the absolute sK + concentration; this is consistent with a recent study demonstrating that HK excursions are associated with mortality, hospitalizations and cardiovascular events in patients receiving haemodialysis [ 26 ]. It should be noted that no association between sK + variability and adverse outcomes was seen in patients on dialysis in the present study; however, the dialysis cohort was comparatively small, which led to wide CIs, limiting the conclusions that could be drawn.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study also demonstrated that increased sK + variability may be a risk factor for MACE compared with low sK + variability, independent of the absolute sK + concentration; this is consistent with a recent study demonstrating that HK excursions are associated with mortality, hospitalizations and cardiovascular events in patients receiving haemodialysis [ 26 ]. It should be noted that no association between sK + variability and adverse outcomes was seen in patients on dialysis in the present study; however, the dialysis cohort was comparatively small, which led to wide CIs, limiting the conclusions that could be drawn.…”
Section: Discussionsupporting
confidence: 92%
“…One recent study showed that a proportion of patients suffer frequently recurrent HK events [ 22 ], potentially leading to patients spending a high proportion of their time in an HK state. Other previous studies of patients in the intensive care unit (ICU) or receiving dialysis have demonstrated that increased sK + variability is associated with increased mortality [ 23–25 ], while another study in patients receiving haemodialysis demonstrated an association between HK excursions and adverse clinical outcomes [ 26 ]. This study aimed to explore the impact of length of time spent in an HK state, defined by thresholds of sK + 5.0, ≥5.5 or 6.0 mmol/L, on adverse clinical outcomes and to investigate sK + variability as a risk factor for adverse clinical outcomes independent of mean sK + in real-world cohorts of patients with cardiorenal conditions and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the DOPPS study showed that serum potassium above 6.0 mEq/L increased arrhythmia by 21% and all-cause mortality by 12 to 33%. 9,17 Our results should raise the awareness of the nephrology community to this common life-threatening condition.…”
Section: Discussionmentioning
confidence: 75%
“…A total of 1021 distinctive studies were found, of which eight studies (between 1998 and 2021) satisfied the inclusion criteria and were comprised in the study [26][27][28][29][30][31][32][33]. The eight studies included 92 558 subjects with chronic kidney disease at the start of the study; 41 474 of them were provided with nutritional potassium limitation and 510 084 were nonrestricted diet.…”
Section: Resultsmentioning
confidence: 99%